Early age carbonation curing for precast reinforced concretes. (15th June 2016) - Zhang, Duo; Shao, Yixin
Highlights: Early age carbonation curing is developed for precast reinforced concrete. Carbonation curing forms carbonate-rich surface with higher electric resistivity. Carbonated concrete (pH > 12) is not more vulnerable to weathering carbonation. The process has shown environmental, technical and economical benefits. Abstract: Carbonation is considered detrimental to reinforced concrete. However if carbonation is performed at early age through curing, the process could be beneficial. This paper is to present a study on a unique process that is developed for early age carbonation curing of precast reinforced concrete to maximize the performance improvement and the carbon storage capacity. The process includes vibration casting, in-mold curing, off-mold preconditioning, carbonation curing and subsequent hydration. It was found that a carbon uptake of 16% based on the cement content could reduce concrete pH to 9.2 on the surface and maintain pH of 13.0 at core immediately after 12 h carbonation. The subsequent hydration was able to increase the pH on surface over 12.3 which was comparable to hydration reference. The carbonated concrete had shown more resistance to permeation by having a higher electrical resistivity on surface and was not more vulnerable to weathering carbonation. The off-mold preconditioning in open air caused no shrinkage cracking because of the controlled evaporation rate. The process makes concrete a sandwich structure with carbonate-rich surface which is responsible for strength gain, carbon storage and durability enhancement and is suitable for precast reinforced concrete production.